ANALISA PEMANFAATAN TEMPURUNG KELAPA SEBAGAI SUBSTITUSI AGREGAT KASAR PADA CAMPURAN BETON TERHADAP KUAT TEKAN BETON - Jerry Sinaga; Qomariah; Taufiq Rochman (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
In this era of very rapid development, construction construction occurs in various places. This also triggers the demand for building materials to increase, not least in terms of concrete construction. Concrete is the main material that is often used in many construction fields such as houses, factories, buildings, bridges, and so on.. The materials used as a mixture are made of materials that are easy to obtain, easy to process, have high durability, and are also durable so they are in great demand in construction.. The Data needed in this study are the results of coarse aggregate testing, fine aggregate testing results, concrete compressive strength testing results, and price requirement analysis results. Analysis of fine and coarse aggregate refers to SNI 03-6820-2002, SNI 1969-2008, ASTM C-556-67, ASTM C-33-74. Mix design analysis refers to SNI-03-2843-2000. Unit price analysis refers to the basic unit price of Malang activities. The results of the analysis show that when checking fine aggregate and coarse aggregate, both aggregates must meet quality requirements. The results showed that, the cost required in the test increases with each variation, inversely proportional to the quality of concrete produced, namely the quality of concrete is not good